2002
DOI: 10.1182/blood-2001-12-0365
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitive fluorescent assays for embryonic and fetal hemoglobin inducers using the human β-globin locus in erythropoietic cells

Abstract: Reactivation of fetal hemoglobin genes has been proposed as a potential therapeutic procedure in patients with ␤-thalassemia, sickle cell disease, or other ␤-hemoglobinopathies. In vitro model systems based on small plasmid globin gene constructs have previously been used in human and mouse erythroleukemic cell lines to study the molecular mechanisms regulating the expression of the fetal human globin genes and their reactivation by a variety of pharmacologic agents. These studies have led to great insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…1A). Consistent with previous findings (31,32), the expression of the ␥ globin promoter-directed DsRed fluorescence was detectable only in the human fetal/embryonic erythroid K562 cells but not in mouse adult erythroid MEL cells (top two rows of panels, Fig. 1B).…”
Section: Setup Of a High-throughput Screening System To Survey Embryosupporting
confidence: 78%
“…1A). Consistent with previous findings (31,32), the expression of the ␥ globin promoter-directed DsRed fluorescence was detectable only in the human fetal/embryonic erythroid K562 cells but not in mouse adult erythroid MEL cells (top two rows of panels, Fig. 1B).…”
Section: Setup Of a High-throughput Screening System To Survey Embryosupporting
confidence: 78%
“…Only samples with efficiencies 475% were considered for analysis. A BAC containing the entire human b-globin locus (pEBAC G gdsREDbEGFP) 39 was digested with HindIII and religated to generate random ligation products of HindIII fragments for transgenic MEL cell experiments ( Supplementary Fig. 6a).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies conducted by our group, hemin and cisplatin have been shown to induce g-globin gene expression while having a minimal effect on b-globin gene expression K562 cells. 39,40 Importantly, following induction of the clonal cell lines carrying the dual reporter constructs, a significant increase in dsRed expression driven by the A g and G g globin promoters was observed, whereas expression from the b-globin promoter consistently produced low levels of EGFP. This result provides further evidence that the transgene expression from the AAVS1-integrated b-globin locus mirrors the expected developmental, stage-specific, globin gene expression profile of normal K562 cells.…”
Section: Kbmentioning
confidence: 99%
“…43 Versions of this BAC clone, G g-A g-EGFP and b-EGFP, which contain the EGFP reporter gene in place of either the g-globin or b-globin genes respectively, have also been previously described. 39,44 In this study, b-EGFP was modified further by replacing the G g-or A gglobin gene with the dsRed reporter gene to generate 'dual reporter' BAC clones. Using homologous recombination, the g-globin genes were replaced with a DNA targeting cassette encoding the dsRed and ampicillin resistance (Amp r ) genes.…”
Section: Vector Constructionmentioning
confidence: 99%